Job stress and employees’ productivity in telecommunication sector of Nigeria - PANKAJ AGARWAL, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
People frequently experience stress while they go about their regular lives at home, school, and work. This study looks at workplace stress and how it affects workers' productivity. Using descriptive data analysis, correlation, and regression analysis using SPSS version 22, five factors that contribute to workplace stress were examined: inadequate working conditions, bullying/harassment, increasing workload, hostile work environment, and downsizing. 110 of the 120 questionnaires that were sent to the employees of MTN, Globacom, Airtel, and Etisalat were successfully completed and returned. The results indicated a bad correlation between employee productivity and job stress. According to the research, employers of labour should take every precaution to make sure that there is no stress at work. Moreover, hiring occupational psychologists and stress management specialists is advised